Konsep Pelestarian Sumber Daya Lahan Pertanian dan Kebutuhan Teknologi - Sumarno Sumarno (Iptek Tanaman Pangan, 2012)
Agricultural lands in Indonesia mostly consist of sloping lands, which succumb to rapid degradation. Agricultural land conservation is defined as: “A total land management system, including a productive and profitable farming operation, integrated with all actions of conservation, preservation and improvement the quality of agricultural lands, coupled with the ecological quality maintenance, to obtain a sustainable production system (TAC 1988). Conservation of agricultural land should meet the following criteria (TAC 1988, Havener 1989): (1) As an integral part of crop production technology and farming system; (2) building farmers’ awareness based on the knowledge, usefulness and advantages of the conservation; (3) applying proper and effective technology in a continuous manner; (4) involving soil-water conservation extension personel; (5) providing a technology demonstration in a form of conservation model; (6) avaiable a reliable handbook easily read by extension workers and by farmers. Extension program for soil and water conservation on agricultural lands becomes an important need in Indonesia, due to the following reasons: (1) degradation of the agricultural lands had occured in all agroecological system; (2) high monsoon rainfall damaging the agricultural resources; (3) agricultural lands mostly situated on the sloping and hilly areas; (4) rapid water flow and relatively short rivers affected high degree of soil erosion; (5) intensive cropping in all year round renders soil susceptible to surface erosion; (6) water absorbtion capacity in the upper water catchment area is low and the top soil is shallow, resulting in erosion and flood; (7) proportion of permanent forest to total land area is small due to the high population density; (8) proportion of poor farmers is high, affecting on exploitative farming practices. The main actors on soil and water conservation are farmers, therefore conservation must be integrated into farming operations. Training on social and technical aspects of soil conservation must be given to the extension agents, so that they are able to develop material for the extension to farmers based on the local needs. Neglecting the extension program on agricultural land-conservation, implying that the government has intentionaly abandon the need on sustainable agriculture for the future generations.